Combination therapies in the management of type 2 diabetes: the use of insulin degludec/liraglutide - Minze MG; Chastain LM (Dove Medical Press, 2016)
Molly G Minze,1 Lisa M Chastain2 1School of Pharmacy, Texas Tech University Health Sciences Center, Abilene, 2Department of Pharmacy Practice, School of Pharmacy, Texas Tech University Health Sciences Center, Dallas, TX, USA Abstract: The global burden of type 2 diabetes is estimated to currently affect over 350 million people worldwide and is anticipated to continue increasing over the next 20 years. Current treatment guidelines recommend the choice of pharmacotherapy based upon patient-specific parameters, with combination therapy for patients with a hemoglobin A1c level ≥9%. A new combination therapy of insulin degludec + liraglutide provides a long-acting basal insulin with a glucagon-like peptide agonist. In clinical trials, this combination product has reduced hemoglobin A1c and fasting plasma glucose more than the individual agents alone. Further advantages observed with this combination include weight loss and decrease in hypoglycemia compared to basal insulin alone. Keywords: insulin degludec, liraglutide, type 2 diabetes, basal insulin, glucagon-like peptide agonist, injectable therapies